ChemInform Abstract: Surfactant CTAB‐Assisted Synthesis of Li1.13 [Ni0.233Mn0.534Co0.233] 0.87O2 with Festoon‐Like Hierarchical Architectures as Cathode Materials for Li‐Ion Batteries with Outstanding Performance. Issue 47 (6th November 2014) - Hou, Xianhua; Zou, Xiaoli; Huang, Yanling; Hu, Shejun; Ru, Qiang; Gao, Yumei
Abstract The layered title cathode material is synthesized from mixtures of precursors (obtained by coprecipitation with Na2CO3 from aqueous solutions containing MnSO4, NiSO4, CoSO4, and different additives such as NH4OH, H2O2, or hexadecyl trimethylammonium bromide at 60 °C for 4 h) and Li2CO3 (850 °C, 24 h).